A microfluidic system based on the monoclonal antibody BCMab1 specifically captures circulating tumor cells from bladder cancer patients. Issue 9 (12th June 2020) - Wang, Yunchao; Liu, Qing; Men, Tongyi; Liang, Ye; Niu, Haitao; Wang, Jianning
Abstract: Circulating bladder tumor cells provide significant information for cancer diagnosis, tumor staging and personalized cancer therapy. Previous studies have reported various methods for capturing circulating tumor cells; however, capturing circulating tumor cells remain a challenge. Here, we present a microfluidic chip with high specificity and capture yields that we refer to as a bladder cancer diagnosis chip. We show that this chip can be used to effectively capture circulating bladder cancer cells based on antibody-BCMab1, a monoclonal antibody that binds to aberrantly glycosylated integrin a3b1. This capture platform is composed of a polydimethylsiloxane (PDMS) chip, whose microchannels are functionalized with biotinylated BCMab1. To change the direction of flow to increase cell-substrate contact, we also introduced a herringbone or chevron channel pattern into the chip. Using this system, we were able to capture bladder cancer cells with high specificity. The capture rates of the bladder cancer diagnosis chip were evaluated at different flow rates and cell concentrations. We found that 90% of the cancer cells were successfully captured at flow rates of 10 μL/min and at various cell concentrations. This highly specific microfluidic chip is a novel tool for bladder cancer diagnosis and offers an opportunity for personalized treatment.